PERAN KOHESIVITAS DALAM TIM OLAHRAGA UNTUK MEMPREDIKSI KEBERHASILAN KELOMPOK - Risna Febriani (Jurnal Terapung : Ilmu - Ilmu Sosial, 2022)
The purpose of this article is to highlight cohesion research stemming from sports investigations. There is a lot of literature on cohesion to explain phenomena in team sports. Research conducted on physical activity on cohesion and other topics in group dynamics (eg, leadership, roles, and norms) has the potential to offer much of the extant group literature. In addition, a clear definition and conceptualization is needed in researching group cohesion on sports teams, considering that sports groups are different from other groups in social life. In the context of team sports, cohesion can be influenced and influenced by the group. Group cohesion can be a factor in team success, but it can also be a result of team performance. Therefore, future research may be able to clarify the direction of the relationship of group cohesion in sports team success Keywords: The role of cohesiveness, predicting group success